UMP students represent the country to Asian Technological University Network Student Leader Forum 2023 - Muhammad Aizat, Azed (2023)
SURABAYA, 17 May 2023 - The Asian Technological University Network (ATU-Net) Student Leader Forum 2023 which took place at Universitas Airlangga Surabaya Indonesia as the host on 15-17 May saw the participation of two representatives of the Students’ Representative Council (MPP) of Universiti Malaysia Pahang (UMP), namely the Vice-President of the Corporate Communications Department, Ahmad Zulfakhrol Helmi Zamri and the Secretary of the Student Services Department from the Faculty of Civil Engineering Technology (FTKA), Muhammad Shafiq Danial Eizmeer Johar.